Parental Involvement and Academic Achievement: A Meta-analysis - Fatimaningrum, Arumi Savitri (Faculty of Psychology, Universitas Negeri Yogyakarta, 2021)
This study examined the relationship between parental involvement and academic achievement through the meta-analysis technique. A total of 40 studies from 18 journal articles that fulfilled the inclusion criteria were analyzed to find the correlation between variables. The result showed the correlation between parental involvement with academic achievement with r=0.251. The result could be concluded that there was a significant correlation between parent involvement and academic achievement. The estimated correlation value of this study is consistent with the previous meta-analysis studies on a similar topic.